Efektifitas Bahan Mikro Organisme Lokal (Mol) terhadap Pertumbuhan dan Hasil Bawang Merah (Allium ascalonikum L.) - Adrianus Antoin Kunja (Fakultas Pertanian, Universitas Timor, 2020)
The need for onions by the people from year to year has increased but productivity has declined. Thus, the productivity of domestic shallots, especially in the TTU district, needs to be increased. Increasing the productivity of shallots needs the absorption of appropriate technology. The purpose of this study was to determine the type of local micro-organisms and the appropriate frequency of watering on the growth and yield of shallots as well as to determine the incidence and severity of disease. This research used factorial Randomized Block Design (RBD), with three replications. The first factor is the type of mole consisting of three levels, namely: control, mole of bamboo root, mole of banana weevil and the second factor is the frequency of watering, namely: once a week, once every two weeks and once every three weeks. The results showed that there was an interaction between the treatment of local micro-organisms and the frequency of MOL watering on the dry weight observation parameters per plot and the severity of the disease, while the other observation parameters did not interact. Local microorganism ingredients that can increase the growth and yield of shallots are local microorganism (MOL) banana weevil with the right frequency for application of MOL banana weevil is once every 3 weeks. Shallots that were applied with MOL were able to reduce the incidence and severity of disease compared to controls